The evaluations on scheduling and routing of Maju stage bus services in Dato'Onn area towards Johor Bahru city status / Norhayati Abd.Rahman - Abd.Rahman, Norhayati (1994)
The proper planning on scheduling and routing is the most important aspect of giving a good service quality in running the transport business., It plays a vital role in attracting the demand of the passengers,SPMB as one of the transport operators, who run the passengers transport business do not deny the importance of a proper scheduling and routing arrarigements . SPMB also is not the only bus operator in Dato'Onn area, There are another two other bus companies operating, so that there are some routes where SPMB has to share the services with these t,wo companies.. They act as a. competitors to SPMB. So, the failure in provic!ing enough services wi 11 resu 11 in the passengers shifting to their cornpetitors., , Qu.estionnaires were distr ibuted in order to f ind out the passengers' perception on the Maju stage bus services in Dato'Orm area. The questionnaires revealed the users' opinions on the Maju stage bus services., These opinions vary, however on the whole the quality of service is fairly good.